The level of basic motor skills rugby players club "Rugby Unisław" - Pabianek, Łukasz; Stępniak, Robert; Pochylski, Cezary (Journal of Education, Health and Sport, 2017)
Introduction: The aim of the study was to evaluate the level of basic motor skills of young players "Club Rugby Unisław" and an indication of the relationship between carrying out tests of physical fitness to the actual effectiveness of the players during the match on the basis of studies and consultations with the coach of the team. For the study indicated were decisive for rugby players, motor skills :, endurance, strength, coordination and flexibility, which matched the appropriate research methods and tests. The tests were conducted using two tests, was tested endurance cardio - respiratory using "beep" test and the speed in the race at 30m, where it has been well studied power measurements athletes. Results: Checking the speed of the players was to have run the 30m distance in the shortest time. The study was attended by 12 players. The test is performed twice. Measurement was made at the time of 5m, 10m and 30 meter. The fastest runner in the fifth meter received a score of 1,168s., The slowest 1,418s. The difference between them was 0,25s. On the second measuring point (10m), the best result was achieved by the test, which was also the fastest on the first accordance with clause measurement of time (5m) and obtained 2,052s. The worst result recorded on a 10m 2,392s. performance difference was 0,34s. On the last point of measurement of time (30m), the best result was achieved by the test, which was not the fastest on the first two measuring points and his total time while trying to 5.319s. The worst result of the test was 0.996s. weaker than the best and was 6,315s. In an attempt to assess the ability of cardiopulmonary also noted considerable discrepancies. The best tested ran 1560m and in accordance with the tables has been rated above normal. Most respondents achieved results at the secondary level. The weakest result in the test is 480 meters. The difference between the best and the worst was examined 1080m. Summary: Most of the players with the best results in tests, as many as five, is in constant composition and regularly scores points. The exception is the two subjects who achieved the weakest results in tests. But they are endowed with considerable strength and good technique game for his age, on a permanent basis, therefore, the main feed and their performance in the game is reflected mainly in the formation of the mill.